2017
DOI: 10.1016/j.ijscr.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Report of two cases of large cell neuroendocrine carcinoma of duodenal ampulla with contrasting outcomes following pancreaticoduodenectomy according to the use of adjuvant chemotherapy

Abstract: HighlightsLarge-cell neuroendocrine carcinoma (LCNEC) of the duodenal ampulla is very rare.LCNEC of the duodenal ampulla behaves aggressively, and the prognosis is poor.Early postoperative tumor relapse occurred in our first case of ampullary LCNEC.Use of adjuvant chemotherapy after surgery resulted long survival in second case.Surgery and adjuvant chemotherapy are recommended for ampullary LCNEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ampullary LCNECs in the literature are limited to 24 case reports before ours, as identified by our review to date ( Table 2 ) [ 11 , 18 , 24 , 26 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Only 14 cases were pure LCNECs [ 24 , 26 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 66 ], while the other 11 had other components [ 11 , 18 , 26 , 59 , 60 , 65 , 66 , 68 ]. Many of these patients had early recurrence with metastases, especially in the liver [ 24 , 56 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ampullary LCNECs in the literature are limited to 24 case reports before ours, as identified by our review to date ( Table 2 ) [ 11 , 18 , 24 , 26 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Only 14 cases were pure LCNECs [ 24 , 26 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 66 ], while the other 11 had other components [ 11 , 18 , 26 , 59 , 60 , 65 , 66 , 68 ]. Many of these patients had early recurrence with metastases, especially in the liver [ 24 , 56 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 14 cases were pure LCNECs [ 24 , 26 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 66 ], while the other 11 had other components [ 11 , 18 , 26 , 59 , 60 , 65 , 66 , 68 ]. Many of these patients had early recurrence with metastases, especially in the liver [ 24 , 56 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their recommendation is pancreaticoduodenectomy (PD) together with lymph node dissection for a better overall survey [ 7 ]. On the other hand, recent literature emphasizes more on the histopathologic features of the tumor (differentiation grade, small or large cell type) rather than ‘TNM’ or ‘ENETS’ (European Neuroendocrine Tumor Society) staging systems in predicting the overall course and treatment strategy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oncology preferred close follow-up with a conservative approach instead of giving oncotherapy. In a study presented by Naoya Imamura et al [ 8 ], adjuvant chemotherapy after radical resection performed for LCNECs was found with better the overall survey without any relapses in the long term. In ‘The NANETS Consensus Guidelines for the Diagnosis and Management of Poorly Differentiated (High-Grade) Extrapulmonary Neuroendocrine Carcinomas’ which was conducted by Strosberg et al [ 9 ], adjuvant chemotherapy (4–6 cycles of cisplatin or carboplatin and etoposide) is recommended regarding the post-operative treatment of poorly differentiated NECs.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations that can be performed for the diagnosis of NET are upper gastrointestinal endoscopy which is the gold standard [6]. Ultrasound abdomen, endoscopic ultrasonography (EUS) and EUS-fine-needle aspiration and biopsy (EUS-FNAB) can also be done along with other radiological modalities such as computerised tomography (CT) and magnetic resonance imaging (MRI) [8,9]. Surgical intervention includes Whipple's procedure or pancreaticoduodenectomy with Roux-enY anastomosis.…”
Section: Introductionmentioning
confidence: 99%